FACTORS INFLUENCING PURCHASE INTENTION TOWARD ONLINE FOOD DELIVERY SERVICE: THE CASE STUDY OF ELE.ME IN CHINA - Wei Qian Qian; Arti Pandey; Tanawat Teepapal; Komm Pechinthorn; Jirangrug Samarkjarn (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
his study investigates the factors that influence purchase intention of O2O food delivery application, Ele.me, in China. The determinants that were used in this study included; price, convenience, perceived usefulness, perceived ease of use, compatibility, and trust. Descriptive quantitative research was conducted through online survey. The questionnaire was conducted and selected from 418 respondents by using random sampling method. Multiple Linear Regression was applied for hypothesis testing. The result of this study showed that price, convenience, perceived usefulness, perceived ease of use, compatibility, and trust have significant and positive relationships with consumers' purchasing intentions for Ele.me. Furthermore, the findings revealed that convenience (β = 0.271, t = 3.664, p < 0.001) was the most influential factor on consumers’ purchasing intention of Ele.me online food delivery. Research suggestions and recommendations were provided.